Analisis Obstruction Of Justice dalam Perspektif Hukum Pidana - Lubis, Fauziah; PC.Sinaga, Juliana (Universitas Ekasakti, 2023)
The aim of this research is to analyze obstruction of justice from a criminal law perspective. The type of legal research method used in this research is a normative research method. The approach methods that will be applied are the Statute Approach and the Case Approach. The data collection technique uses library research (normative legal research) which focuses on secondary data, so the author conducted research on laws and government regulations relating to this research. Data collection tools in normative juridical research come from secondary data with the aim of obtaining concepts, theories and information as well as conceptual thoughts from previous researchers in the form of statutory regulations, scientific works, journals and others. The data analysis technique begins with examining the collected data, then conducting direct and directed interviews, then conducting qualitative data analysis, that is, the data obtained is arranged systematically and then analyzed qualitatively in the form of rules. The results of this research found that the criminal act of obstruction of justice as regulated in the provisions of Article 21 Article 21 of Law no.31 of 1999 Jo Law no. 20 of 2001 concerning Eradication of Corruption Crimes and Article 22 of Law no. 21 of 2007 concerning the Eradication of the Crime of Human Trafficking is a crime in which the perpetrator commits acts by obstructing the justice process against laws that are actually clear and against law enforcement such as giving false information, committing violence, destroying evidence, premeditated crimes and make threats. As stated in Article 221 paragraph (1), the Criminal Code threatens with criminal penalties for anyone who hides or helps someone who commits a crime so that the person avoids investigation or detention. In the criminal act of obstructing the legal process (obstruction of justice) apart from being viewed from the act which contains a mistake on the part of the perpetrator which must be considered as intentional as intended, and the act is clearly in conflict with the applicable laws and regulations then the act can be is said to be a criminal act/criminal act.